The effect of addition Eriobotrya japonica L. marmalade on physicochemical, microbiological, and sensory properties of probiotic yogurts - Turgut, Tamer; Diler, Abdulkerim (Frontiers in Nutrition, 2023)
This study investigated the effects of loquat (Eriobotrya japonica L.) marmalade (LM) supplementation in probiotic yogurt during a 21-day storage period. In addition, the viability of Bifidobacter and its effect on yogurt quality were investigated. Four types of yogurt, including plain yogurt (LM0) and yogurts with 5%, 10%, and 15% LM were prepared. Physicochemical properties, microbial growth, and textural and sensory properties were investigated on days 1, 7, 14, and 21 of storage. The addition of LM to yogurt significantly affected the total dry matter, fat, pH, titratable acidity, syneresis, water-holding capacity, and color parameters (L*, a*, b*). The addition of LM caused an decrease in L* (from 87.52 to 81.78) and an increase in a* values (from -35.42 to -30.14). Yogurts containing 10% and 15% LM demonstrated lower syneresis than control samples during storage. During storage, the pH values of the yogurts continuously decreased (P <0.01). The viability of Bifidobacteria in yogurt was not affected by LM addition. All yogurts showed a decrease in the viable count of Bifidobacteria spp. during storage. Lactobacillus delbrueckii ssp. bulgaricus decreased more than Streptococcus thermophilus did during the storage period. Coliform bacteria were not detected in the yogurt samples. When a general evaluation was made by considering the physicochemical quality and sensory and textural properties of all yogurt samples, it was revealed that LM- added yogurts could be produced and stored for 21 days.